Tetrakis(μ-2-phenoxypropionato)-κ(3) O,O′:O′;κ(3) O:O,O′;κ(4) O:O′-bis[(1,10-phenanthroline-κ(2) N,N′)(2-phenoxypropionato-κ(2) O,O′)holmium(III)] - Shen, Jin-Bei (International Union of Crystallography, 2011)
The title compound, [Ho(2)(C(9)H(9)O(3))(6)(C(12)H(8)N(2))(2)], lies about a centre of symmetry and is comprised of six 2-phenoxypropionate (POPA) anions and two 1,10-phenanthroline (phen) ligands. The two Ho(III) ions are linked by four POPA groups utilizing both bi- and tridentate bridging modes to form an inversion-symmetric dimer. Each Ho(III) ion is nine-coordinate, with a chelating 1,10-phenanthroline molecule, one bidentate chelating carboxylate group, two bidentate bridging carboxylate groups and two tridentate bridging carboxylate groups in a distorted mono-capped square antiprism geometry. There are weak π–π aromatic interactions between the phen groups and aromatic rings of the POPA ligands [centroid–centroid distance = 3.829 (1) Å].